COVID‐19: Implications for Nursing and Health Care in the United States. Issue 1 (30th December 2022) - Reynolds, Nancy R.; Baker, Deborah; D'Aoust, Rita; Docal, Maria; Goldstein, Nancy; Grubb, Lisa; Hladek, Melissa D.; Koirala, Binu; Kverno, Karan; Ling, Catherine; Lukkahatai, Nada; McIltrot, Kimberly; et al.
Abstract: Purpose: COVID‐19 and other recent infectious disease outbreaks have highlighted the urgency of robust, resilient health systems. We may now have the opportunity to reform the flawed health care system that made COVID‐19 far more damaging in the United States (U.S.) than necessary. Design and Methods: Guided by the World Health Organization (WHO) Health System Building Blocks framework (WHO, 2007) and the socio‐ecological model (e.g., McLeroy et al., 1988), we identified challenges in and strengths of the U.S.' handling of the pandemic, lessons learned, and policy implications for more resilient future health care delivery in the U.S. Using the aforementioned frameworks, we identified crucial, intertwined domains that have influenced and been influenced by health care delivery in the U.S. during the COVID‐19 pandemic through a review and analysis of the COVID‐19 literature and the collective expertise of a panel of research and clinical experts. An iterative process using a modified Delphi technique was used to reach consensus. Findings: Four critically important, inter‐related domains needing improvement individually, interpersonally, within communities, and for critical public policy reform were identified: Social determinants of health, mental health, communication, and the nursing workforce. Conclusions: The four domains identified in this analysis demonstrate the challenges generated or intensified by the COVID‐19 pandemic, their dynamic interconnectedness, and the critical importance of health equity to resilient health systems, an effective pandemic response, and better health for all. Clinical relevance: The novel coronavirus is unlikely to be the last pandemic in the U.S. and globally. To control COVID‐19 and prevent unnecessary suffering and social and economic damage from future pandemics, the U.S. will need to improve its capacity to protect the public's health. Complex problems require multi‐level solutions across critical domains. The COVID‐19 pandemic has underscored four interrelated domains that reveal and compound deep underlying problems in the socioeconomic structure and health care system of the U.S. In so doing, however, the pandemic illuminates the way toward reforms that could improve our ability not only to cope with likely future epidemics but also to better serve the health care needs of the entire population. This article highlights the pressing need for multi‐level individual, interpersonal, community, and public policy reforms to improve clinical care and public health outcomes in the current COVID‐19 pandemic and future pandemics, and offers recommendations to achieve these aims.